Properties of MgCaZr Alloys - Serak, Jan; Simon, Cyril; Vojtech, Dalibor (Manufacturing Technology Journal, 2022)
The use of most commercial magnesium alloys is limited to working at normal temperatures. The excellent ratio between the mechanical properties and the density of magnesium alloys necessarily leads to the development of new types of alloys that would be usable even at elevated temperatures. This would significantly increase the applicability of these alloys where steels or aluminum alloys are still used, especially in the transport industry. The problem with today's high temperature resistant magnesium alloys is the need to use expensive rare earth alloys. Significantly cheaper alloys of magnesium with zirconium and calcium are studied in this work. The microstructure, mechanical properties under pressure at the temperatures of 20, 150, 200 and 250 ° C were studied for several alloys with different contents of Zr and Ca. Furthermore, the stability of alloys during their long-term temperature exposure was studied. A very positive effect of the studied additives on the properties of alloys was found, which gives these alloys a very promising perspective in the future.
Keywords: Magnesium Alloys; Thermal stability; Mechanical Properties; Microstructure; Alloying